Performance of the Regional Innovation Laboratory in Improving the Quality of Makassar City Government - Ali Mardana; Risma Niswaty; Anshari Anshari; Dian Meiliani Yulis (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research is a descriptive study using a qualitative approach. With data collection techniques used are observation techniques, interviews, and documentation. The technique of checking the validity of the data used is the triangulation technique. The data analysis technique used in this study is an interactive model. The results of the study show that the performance of the Partnership-Based Innovation Laboratory (Labinov Beken) has been able to improve the quality of Makassar City Government well, but still needs improvement in supporting its implementation. This is reflected in the input indicators owned by the Partnership-Based Innovation Laboratory (Labinov Beken) which have been good in terms of Human Resources, Financial, and existing regulations that have supported the implementation of this Labinov Beken. When viewed in terms of output indicators, Labinov Beken has given birth to various regional innovations, but there are still Regional Innovation Programs that have not run optimally. In terms of outcome indicators (outcomes), Labinov Beken has been able to provide service satisfaction to the community and accelerate the economy and increase development in the Makassar City Region. Besides that, from the indicators of benefits (benefits), Labinov Beken has provided benefits as a vehicle for stimulating the atmosphere for the birth of innovations that can overcome obstacles to the implementation of programs and activities. Then in terms of impact indicators (impacts), Labinov Beken has had a positive impact with the birth of various regional innovations that have the potential to advance the quality of government, but there is still a negative impact because a small number of ASN are unable to adapt to changing their work style following the development of existing innovations.